A CRITIQUE OF ACCOUNTING TRENDS AND TECHNIQUES–1951 EDITION. - Gregory, Robert H. (The Accounting Review, 1952)
In summary, the following points should be emphasized. Considering the way the research department has defined its project, there are limitations that keep one from drawing valid conclusions about accounting practices of American corporations from the study of 525 corporations. First, the use of corporate annual reports as a source of information is not entirely suitable because they are not designed to give information about accounting practices. Furthermore, they tend to emphasize new and unusual accounting practices at the expense of well-established practices that are more or less taken for granted. Second, the sample of corporations selected for study is heavily weighted with large corporations that are generally served by nation-wide accounting firms. It appears (although substantiating information is not presented here) that the large corporations have more readily adopted new and unusual accounting practices than have the smaller corporations. The two foregoing limitations can be overcome only by making the fundamental changes of adopting a new or supplementary source of information and selecting a new sample of corporations. Other deficiencies of the five surveys that have been pointed out, but that can readily be corrected in future editions, include: lack of comparability of information in individual tabulations; unannounced (and unadjusted for) changes in the sample of corporations included in the survey; and clerical and editorial inaccuracies arising from dropping or adding groups (without revision of the prior years' data) in a tabulation given in one survey when it is repeated in a later survey. Let me repeat the point made at the beginning. Some of the comments may seem to be highly critical. However, all comments are made in a friendly, constructive spirit. It seems only fair.